TANTANGAN PENGEMBANGAN PERTANIAN WILAYAH PEDESAAN (STUDI KASUS DESA LEUKEN) - Helmi Noviar; Arie Saputra; Syahril Syahril; Fitriadi Fitriadi; Saiful Badli (Jurnal Pengabdian Agro and Marine Industry, 2023)
Agriculture is the most importance resources of the economy in rural areas. The development of agricultural commodities in rural areas can no longer be carried out partially. The involvement of various parties that are integrated and support each other must be carried out continuously. Mapping of key aspects that are challenges to agricultural development must be carried out integrally. This paper formulates that there are several key aspects that are challenges to the development of rural agriculture. The challenge is the support of the government, private sector and academia, the development of digital technology in the concept of smart farming and the role of the younger generation. Everything will lead to increased efficiency and effectiveness of game results which will drive the Village economy.